Implementasi Google Apps for Education sebagai Upaya Peningkatan Keterampilan Pendidik di SMP Negeri 20 Kota Bandung - Nugraha, Ios Susila (TSAQOFAH, 2022)
This study aims to improve the skills of educators at SMP Negeri 20 Bandung by applying LMS, namely Google Apps For Education (GAFE). This research is a school action research using a quantitative approach. The population of this research is all teaching staff at SMP Negeri 20 Bandung. The sampling technique used was total sampling, which used the entire population of 46 educators. The data collection technique is a direct observation of the Google Classroom application. Data collection tool in the form of observation sheets. Data collection was carried out three times during the research period: pre-cycle, cycle 1, and 2. The data analysis technique used started with data reduction, data presentation, and concluding. The study results show that the application of the Learning Management System through Google Apps For Education can improve the skills of educators at SMP Negeri 20 Bandung City. The value of pre-cycle skills is 31.46% (very low). After the implementation of cycle 1, the skills of educators increased to 56.17% (high enough); in cycle 2 it also managed to rise to 73.22% (high).